Snowball: a novel gene family required for developmental patterning of fruiting bodies of mushroom-forming fungi (Agaricomycetes) - Csenge Földi; Zsolt Merényi; Bálint Balázs; Árpád Csernetics; Nikolett Miklovics; Hongli Wu; Botond Hegedüs; Máté Virágh; Zhihao Hou; Xiao-Bin Liu; László Galgóczy; László G. Nagy (mSystems, 2024)
ABSTRACTThe morphogenesis of sexual fruiting bodies of fungi is a complex process determined by a genetically encoded program. Fruiting bodies reached the highest complexity levels in the Agaricomycetes; yet, the underlying genetics is currently poorly known. In this work, we functionally characterized a highly conserved gene termed snb1, whose expression level increases rapidly during fruiting body initiation. According to phylogenetic analyses, orthologs of snb1 are present in almost all agaricomycetes and may represent a novel conserved gene family that plays a substantial role in fruiting body development. We disrupted snb1 using CRISPR/Cas9 in the agaricomycete model organism Coprinopsis cinerea. snb1 deletion mutants formed unique, snowball-shaped, rudimentary fruiting bodies that could not differentiate caps, stipes, and lamellae. We took advantage of this phenotype to study fruiting body differentiation using RNA-Seq analyses. This revealed differentially regulated genes and gene families that, based on wild-type RNA-Seq data, were upregulated early during development and showed tissue-specific expression, suggesting a potential role in differentiation. Taken together, the novel gene family of snb1 and the differentially expressed genes in the snb1 mutants provide valuable insights into the complex mechanisms underlying developmental patterning in the Agaricomycetes.IMPORTANCEFruiting bodies of mushroom-forming fungi (Agaricomycetes) are complex multicellular structures, with a spatially and temporally integrated developmental program that is, however, currently poorly known. In this study, we present a novel, conserved gene family, Snowball (snb), termed after the unique, differentiation-less fruiting body morphology of snb1 knockout strains in the model mushroom Coprinopsis cinerea. snb is a gene of unknown function that is highly conserved among agaricomycetes and encodes a protein of unknown function. A comparative transcriptomic analysis of the early developmental stages of differentiated wild-type and non-differentiated mutant fruiting bodies revealed conserved differentially expressed genes which may be related to tissue differentiation and developmental patterning fruiting body development.